2003
DOI: 10.1007/s11748-003-0032-5
|View full text |Cite
|
Sign up to set email alerts
|

Aortic root replacement for prosthetic aortic valve detachment without regurgitation and with englarged Valsalva’s sinuses and complete atrioventricular block caused by Takayasu’s aortitis

Abstract: We replaced the aortic root in a 43-year-old woman with Takayasu's aortitis associated with prosthetic aortic valve detachment. The patient's aortic valve had been replaced when she was 31 years old with a mechanical prosthesis to treat aortic regurgitation. Though C-reactive protein was kept almost normal with prednisolone, complete atrioventricular block suddenly appeared 12 years after the first operation. After the implantation of an artificial pacemaker, we closely followed up aortic root status. Aortogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…[12,14,15,20,23,24,28,[30][31][32]47] The degree of AR was not reported in 118 patients (74.2%). [10,16,18,22,26,35,38,45,50] In the remaining 41 patients (25.8%), one (2.4%) was mild, [29] nine (22.0%) were moderate, [11,12,23,34,37,41,42,49] one (2.4%) was moderate-to-severe [37] and 30 (73.2%) were severe [13][14][15]17,[19][20][21]24,25,27,28,[30][31][32][33]36,39,40,[42][43][44]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[12,14,15,20,23,24,28,[30][31][32]47] The degree of AR was not reported in 118 patients (74.2%). [10,16,18,22,26,35,38,45,50] In the remaining 41 patients (25.8%), one (2.4%) was mild, [29] nine (22.0%) were moderate, [11,12,23,34,37,41,42,49] one (2.4%) was moderate-to-severe [37] and 30 (73.2%) were severe [13][14][15]17,[19][20][21]24,25,27,28,[30][31][32][33]36,39,40,[42][43][44]…”
Section: Resultsmentioning
confidence: 99%
“…[48] In 33 patients (20.8%), the type of TA could be tracked: five (15.2%) were type 1, [28,33,34,37,47] 21 (63.6%) were type 2a, [11][12][13][14][17][18][19][20][21][22][23][24]27,29,30,36,38,39,46,48,49] one (3.0%) was type 2b, [31] three (9.1%) were type 3, [32,40,41] two (6.1%) were type 4, and one (3.0%) was type 5. [16] The activity of TA could be traced in 42 patients (26.4%): 37 (88.1%) were active [12,[14][15][16][18][19][20][21][22][23][24]26,28,[30][31][32]36,37,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A few cases of cardiac conduction disturbance due to the extension of aortitis have been reported (3,4). Watanabe et al (3) and Yokoi et al (4) reported that the possibility of conductance disturbance was caused by a myocarditis-attributable disease.…”
Section: Discussionmentioning
confidence: 99%